Participation of non-aminoisobutyric acid (Aib) residues in the 310 helical conformation of Aib-rich foldamers: a solid state study. (8th January 2015) - Pike, Sarah J.; Boddaert, Thomas; Raftery, James; Webb, Simon J.; Clayden, Jonathan
Abstract : 310 helical conformations that extend over 21 Å result when selected non-Aib terminal and central residues are incorporated into Aib-rich foldamers. Abstract : The solid state conformational preferences of a series of 2-aminoisobutyric acid (Aib) foldamers bearing a single N-terminal tertiary amino acid (Cbz-l -phenylalanine (Cbz-l -Phe)) have been investigated by X-ray crystallography. The type of β-turn present at the N-terminus and the global screw-sense preferences of the Aib foldamers were determined by analysis of intramolecular hydrogen-bonds and peptide torsion angles. The contrasting influence of a C-terminal ester or amide on the 310 helical conformation of the foldamers was established by identifying the hydrogen-bonding motifs adopted in the solid state. The ability of non-Aib achiral quaternary residues in the middle of the chain to stabilise the 310 helix was similarly confirmed. Combining these structural features, which promote the formation of consecutive i → i + 3 β-turns in Aib foldamers, permitted the formation of long chain oligomers in 310 helical conformations that extend over 21 Å.